Impact of Washing with Antioxidant-Infused Soda–Saline Solution on Gel Functionality of Mackerel (Auxis thazard) Surimi - Porntip Thongkam; Manat Chaijan; Ling-Zhi Cheong; Worawan Panpipat (Foods, 2023)
Mackerel (Auxis thazard), a tropical dark-fleshed fish, has the potential to be used in the production of surimi. It is necessary to identify the optimal washing method to make better use of this species since efficient washing is the most important step in surimi processing to ensure maximal gelling and high-quality surimi. The purpose of this study was to evaluate the combined effect of cold carbonated water (CW) with NaCl and antioxidants in washing media, so-called antioxidant-infused soda–saline solution, on lipid and myoglobin removal efficacy, biochemical characteristics, gelling properties, sensory features, and the oxidative stability of mackerel surimi in comparison with unwashed mince (T1) and conventional water washed surimi (T2). Mackerel mince was washed with CW in the presence of 0.6% NaCl at a medium to mince ratio of 3:1 (v/w) without antioxidant (T3) or with the addition of 1.5 mM EDTA plus 0.2% (w/v) sodium erythorbate and 0.2% sodium tripolyphosphate (T4), 100 mg/L gallic acid (T5), and 5 mM citric acid containing 8 mM calcium chloride (T6). During the first washing cycle, the antioxidants were mixed into the washing medium. The second and third washing cycles were then completed with cold water. The yields of all treatments were roughly 75–83%, based on the gross weight of the raw mince. The pH of the surimi was in a range of 5.47–6.46. All of the surimi had higher reactive sulfhydryl (SH) content and surface hydrophobicity but lower Ca2+-ATPase activity than unwashed mince (p < 0.05). After washing, lipids decreased significantly (p < 0.05), accounted for a 65–76% reduction. The T2 surimi had the highest peroxide value (PV). T1 had the lowest conjugated diene value. T1 and T4 surimi had the lowest TBARS value (p < 0.05). A lower non-heme iron level was found in all antioxidant-treated samples than in T1. Washing can increase the redox stability of myoglobin regardless of the washing media, as seen by the relatively low metmyoglobin levels. According to the dynamic viscoelastic behavior, all surimi and unwashed mince underwent the same degree of sol–gel transition following heat gelation. T1 showed the lowest breaking force, deformation, gel strength, and whiteness (p < 0.05). Surimi made from T4 or T5 had the highest gel strength when both breaking and deformation were considered, but the latter’s expressible drip was noticeably higher. Surimi gel appears to be stabilized against lipid oxidation, as demonstrated by low PV and TBARS levels, when produced with T4. Because of the low level of TBARS, all 10 panelists rated rancid odor as low (~1 out of 4), with no significant variations across treatments. Only treatments with T4 and T6 tended to have a lower fishy odor score as compared to unwashed mince. Scanning electron microscope demonstrated that surimi gels washed with all washing media exhibited microstructures that were very comparable, with the exception of the T6 treatment, which had big pores and aggregates. Based on the quality features, T4 appeared to be the optimal medium to enhance the gel functionality of mackerel surimi.